Design of Restrictive Conditions for Simultaneous Loading and Unloading of Goods with Different Temperature Regimes in Vehicle Routing Problem - Kleprlík, Jaroslav; Brázdová, Markéta (My University, 2024)
This paper deals with the vehicle routing problem involving simultaneous loading and unloading of goods with different temperature regimes. Existing modifications of the problem as well as current software products do not focus on the transport of goods with different temperature regimes. In this paper, restrictive conditions for the joint transportation of goods with multiple temperature regimes are determined, which can be used within various types of optimization algorithms that address vehicle routing problems. Considering the proposed conditions in these algorithms will increase the utilization of the vehicle payload, and load space while complying with the established mandatory rules for the transport of foodstuffs. This will reduce the number of journeys required to carry out the transport, thus resulting in savings in operating costs.
Návrh omezujících podmínek pro současnou nakládku a vykládku zboží s různými teplotními režimy v problému trasování vozidel
Keywords: Operational research; vehicle routing problem; simultaneous loading and unloading; new restrictive condition; multiple temperature regimes; Operační výzkum; současná nakládka a vykládka; nová omezující podmínka; více teplotních režimů